1983
DOI: 10.1021/ja00344a064
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of unimolecular ionic decompositions by deuterium and heavy-atom isotope effects. Concerted elimination of acetaldehyde from the benzyl ethyl ether radical cation

Abstract: Partial support for the purchase of a Bruker WP-200 NMR spectrometer from the National Science Foundation is also acknowledged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Unlike deprotonated pinacol itself, deprotonated benzpinacol does undergo a pinacol-type rearrangement, presumably because of (i) the formation of the strong intramolecular hydrogen bond shown in Eqn (15) and (ii) the ease of phenyl rnigrati~n.~' R R [3,3] Rearrangements like the oxy Cope [Eqn (16)I4l and Claisen rearrangement42 are facile reactions, and occur in both the condensed and gas phases. [1,3] Rearrangements [Eqn (17)] do occur in the condensed phase, but are not observed in the gas phase when R is alkyl or aryl. In contrast, if the vinylidene alkoxide system contains a small ring, the gas-phase [1,3] rearrangement does occur.…”
Section: Intramolecular Rearrangement Reactions Of Even-electron Anionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike deprotonated pinacol itself, deprotonated benzpinacol does undergo a pinacol-type rearrangement, presumably because of (i) the formation of the strong intramolecular hydrogen bond shown in Eqn (15) and (ii) the ease of phenyl rnigrati~n.~' R R [3,3] Rearrangements like the oxy Cope [Eqn (16)I4l and Claisen rearrangement42 are facile reactions, and occur in both the condensed and gas phases. [1,3] Rearrangements [Eqn (17)] do occur in the condensed phase, but are not observed in the gas phase when R is alkyl or aryl. In contrast, if the vinylidene alkoxide system contains a small ring, the gas-phase [1,3] rearrangement does occur.…”
Section: Intramolecular Rearrangement Reactions Of Even-electron Anionsmentioning
confidence: 99%
“…[1,3] Rearrangements [Eqn (17)] do occur in the condensed phase, but are not observed in the gas phase when R is alkyl or aryl. In contrast, if the vinylidene alkoxide system contains a small ring, the gas-phase [1,3] rearrangement does occur. For example, the collisioninduced spectra of deprotonated 1-vinylcyclobutanol and cyclohexanone are identical [see Eqn (18)];43 the fragmentation is exclusively that of deprotonated cyclohexanone.…”
Section: Intramolecular Rearrangement Reactions Of Even-electron Anionsmentioning
confidence: 99%
“…In particular, an extensive experimental investigation, utilizing both 13 C and 2 H kinetic isotope effects, clearly indicated that the McLafferty rearrangement of ketone radical cations is stepwise. 9 However, Stone et al 7 proposed a concerted mechanism for the loss of acetaldehyde from the benzyl ethyl ether radical cation, which is also a McLafferty type reaction, in collisional activation spectra measurements. A few years later, the same group of authors 8 confirmed this observation by using Rice-Ramsperger-Kassel-Marcus (RRKM) theory on the same reaction.…”
Section: Introductionmentioning
confidence: 99%
“…More evidence for this rearrangement reaction was found with the decomposition of ionized aliphatic aldehydes, ketones, esters, amides and other derivatives with observation of elimination of vinyl hydrocarbons . The origin of γ‐hydrogen transfer has been established by extensive experiments involving deuterium and heavy‐atom labeling . McLafferty proposed the electronic mechanism for this type of rearrangement reaction, involving γ‐hydrogen transfer.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] The origin of g-hydrogen transfer has been established by extensive experiments involving deuterium and heavy-atoml abeling. [8][9][10] McLafferty proposed the electronic mechanism for this type of rearrangement reaction, [11,12] involv-ing g-hydrogent ransfer.T his type of reactionw as nameda fter him and hasb een reported generally for other chemical systems. [13][14][15][16][17][18][19][20] Aromatic ethylamines are fundamentalc hemical materials and include phenethylamine-derivedn eurotransmitters.…”
Section: Introductionmentioning
confidence: 99%